Lower FGFR2 mRNA Expression and Higher Levels of FGFR2 IIIc in HER2-Positive Breast Cancer - Dix-Peek, Thérèse; Dickens, Caroline; Valcárcel, Juan; Duarte, Raquel A. B. (Biology (Basel, Switzerland), 2024)
Fibroblast growth factor receptor 2 (FGFR2) has been associated with breast cancer. We performed in silico analyses to investigate the FGFR2 mRNA expression and splice variants associated with breast cancer subtypes. Online databases, including cBioPortal and TCGA SpliceSeq, were used to examine the association between the FGFR2 expression and splice variants with breast cancer subtypes. A higher FGFR2 mRNA was significantly associated with luminal, oestrogen receptor (ER)-positive breast cancers, and invasive lobular carcinomas, whereas a lower FGFR2 was associated with human epidermal growth factor receptor 2 (HER2)-positive breast cancer and invasive ductal carcinomas. The epithelial alternatively spliced FGFR2 IIIb isoform was significantly enriched in ER+ breast cancer, while the mesenchymal FGFR2 IIIc isoform was significantly prevalent in HER2+ cancer. Increased levels of FGFR2 and IIIb splice isoforms are associated with less aggressive breast cancer phenotypes, while decreased levels of FGFR2 and increased IIIc splice isoform are associated with more aggressive phenotypes.